DEIKSIS DALAM FILM THE BOSS BABY KARYA TOM MCGRATH: SUATU ANALISIS PRAGMATIK - WENUR, FERGY J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACTS Â Â ThisÂ  researchÂ  â€œ DeiksisÂ  dalamÂ  Film The BossÂ  BabyÂ  karyaÂ  TomÂ  McGrathâ€.Â  ThereÂ  areÂ  5Â  typesÂ  ofÂ  deixis,Â  those are:Â  personÂ  deixisÂ  (firstÂ  person,Â  secondÂ  person,Â  andÂ  thirdÂ  person),Â  placeÂ  deixis,Â  timeÂ  deixis,Â  discourseÂ  deixis,Â  andÂ  socialÂ  deixis.Â  DeixisÂ  belongsÂ  toÂ  pragmaticsÂ  theÂ  wordÂ  deixisÂ  comeÂ  fromÂ  theÂ  GreekÂ  deiktikos,Â  itâ€ŸsÂ  means,Â  â€žpointingâ€Ÿ. Â TheÂ  objectiveÂ  ofÂ  thisÂ  researchÂ  areÂ  toÂ  identifyÂ  andÂ  classifyÂ  theÂ  typesÂ  ofÂ  deixisÂ  andÂ  toÂ  analyzeÂ  theÂ  usageÂ  ofÂ  deixisÂ  inÂ  theÂ  filmÂ  TheÂ  BossÂ  BabyÂ  byÂ  TomÂ  McGrath.Â  TheÂ  methodÂ  usedÂ  inÂ  thisÂ  researchÂ  isÂ  descriptiveÂ  method.Â  TheÂ  dataÂ  areÂ  identified,Â  classifiedÂ  andÂ  analyzedÂ  descriptively.Â  TheÂ  dataÂ  wereÂ  analyzedÂ  basedÂ  onÂ  LevinsonÂ  theory. Â TheÂ  resultÂ  showsÂ  thatÂ  thereÂ  areÂ  fiveÂ  typesÂ  ofÂ  deixisÂ  inÂ  theÂ  filmÂ  TheÂ  BossÂ  Baby,Â  thoseÂ  areÂ  personÂ  (firstÂ  person: I,Â  me,Â  our,Â  we,Â  andÂ  my;Â  secondÂ  person: yourÂ  andÂ  you;Â  thirdÂ  person:Â  he,Â  him,Â  they,Â  andÂ  them),Â  placeÂ  deixis:Â  here,Â  house,Â  overÂ  hereÂ  andÂ  where,Â  timeÂ  deixis:Â  time,Â  Monday,Â  07.00Â  A.M,Â  now,Â  weeks,Â  ever,Â  faster,Â  yearsÂ  ago,Â  days,Â  Friday,Â  andÂ  longÂ  timeÂ  ago,Â  discourseÂ  deixis:Â  this,Â  that,Â  andÂ  this,Â  andÂ  socialÂ  deixis:Â  brother,Â  maâ€Ÿam,Â  mom,Â  dad,Â  sir,Â  bigÂ  bossÂ  baby,Â  mr.Â  ladyÂ  man,Â  boss,Â  andÂ  ladies,Â  whearesÂ  theÂ  usageÂ  ofÂ  deixisÂ  foundÂ  inÂ  theÂ  filmÂ  areÂ  symbolÂ  andÂ  gesturalÂ  usage. Â ItÂ  isÂ  expectedÂ  thatÂ  thisÂ  researchÂ  willÂ  helpÂ  theÂ  studentsÂ  andÂ  theÂ  otherÂ  readersÂ  toÂ  learnÂ  theÂ  pragmaticsÂ  aspects,Â  especiallyÂ  aboutÂ  deixis. Keywords:Â  Film,Â  Pragmatics,Â  Deixis.